A Proof-of-Concept Study on Smart Gloves for Real-Time Chest Compression Performance Monitoring - Guridi, Sofia (IEEE, 2025)
Correctly performed Cardiopulmonary Resuscitation (CPR) is a critical element in preventing deaths caused by cardiac arrest (CA). To improve the outcomes and quality of CPR, stand-alone devices that monitor the performance and provide feedback have been developed. However, these devices have multiple limitations due to their rigidity and stiffness. Furthermore, most of the devices do not account for complete chest recoil as a metric of quality CPR, reducing the quality of compressions. To overcome these limitations, this study proposes smart gloves equipped with e-textiles-based pressure sensors and inertial measurement units (IMUs) to monitor the quality adult CPR in real-time. The prototype development combined data-driven design and Research Through Design (RtD) methods, taking into account not only the accuracy but also the usability of the smart gloves. A preliminary study with nine participants performing CPR on a doll was conducted to evaluate the accuracy and wearability of the smart gloves. Study results show that the smart gloves accurately detect chest compression parameters, including compression depth, compression rate, chest recoil and interruption between compressions based on the intelligent fusion of pressure sensors and IMUs. In addition, the newly developed smart gloves are lightweight, hand adaptable, and easily replicable as an alternative for hard case devices. The design methods used in this study can be applied to design other accessible and comfortable wearable devices in healthcare settings. © 2013 IEEE.